Effect of Work Environment and Motivation on Employee Performance at PT. Karya Mandiri Gresik - Kartiko, Ari; Sirojuddin, Akhmad (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2020)
The establishment of the company aims to get maximum benefit. Competition for maximum profit can be achieved if the company has good performance. Capital facilities and infrastructure, technology and applicable regulations require human resources Performance is closely related to human resources in the company. Human performance is greatly influenced by the work environment and motivation of an employee in carrying out their work. The influence of the work environment and one's motivation at work can be investigated through a quantitative approach that aims to find out how the influence of the work environment and work motivation on performance and find out which has the dominant influence of the two variables. In the research conducted at PT. Karya Mandiri, it addressed the results that one's work motivation has a more dominant influence on employee performance. It can be from a work motivation value of 0.523 while the influence of the work environment on performance is only 0.128. This primary data is obtained by distributing questionnaires to all employees and then the data is processed using software.